Singular Sheet Etching of Graphene with Oxygen Plasma - Al-Mumen, Haider; Rao, Fubo; Li, Wen; Dong, Lixin (Nano-Micro Letters, 2014)
This paper reports a simple and controllable post-synthesis method for engineering the number of graphene layers based on oxygen plasma etching. Singular sheet etching (SSE) of graphene was achieved with the optimum process duration of 38 seconds. As a demonstration of this SSE process, monolayer graphene films were produced from bilayer graphenes. Experimental investigations verified that the oxygen plasma etching removes a single layer graphene sheet in an anisotropic fashion rather than anisotropic mode. In addition, etching via the oxygen plasma at the ground electrodes introduced fewer defects to the bottom graphene layer compared with the conventional oxygen reactive ion etching using the powered electrodes. Such defects can further be reduced with an effective annealing treatment in an argon environment at 900–1000°C. These results demonstrate that our developed SSE method has enabled a microelectronics manufacturing compatible way for single sheet precision subtraction of graphene layers and a potential technique for producing large size graphenes with high yield from multilayer graphite materials.